INFECTIOUS COMPLICATIONS CAUSED BY NON-SPOREFORMING ANAEROBIC BACTERIA IN CANCER PATIENTS. RELEVANCE OF THE PROBLEM - I. V. Tereshchenko; Z. V. Grigoryevskaya; I. N. Petukhova; N. S. Bagirova; V. D. Vinnikova; V. A. Vershinskaya; N. V. Dmitrieva (Сибирский онкологический журнал)
The purpose of the study: to identify the significance of anaerobic bacteria and analyze their role in the development of infectious complications in cancer patients. Material and Methods. The review includes data from clinical and in vitro studies published in Russian and international press for the period from 1989 to 2018. Results. Data analysis has shown that many aspects related to anaerobic non-sporeforming bacteria are insufficiently studied, although they can cause severe hospital infections. This is especially true for patients with immune system defects, including cancer patients. In this category of patients, anaerobic bacteria can cause infections of the maxillofacial region, intra-abdominal infections, lower respiratory tract infections, urinary infections, and blood flow infections. In cancer patients, infectious complications are more severe, and may adversely affect treatment outcomes. A long process of anaerobic cultivation dictates the need for empirical treatment of infection for an average of 6 to 7 days. Since the middle of the last century, metronidazole was the «gold standard» of therapy. However, today the situation has changed dramatically. More than 80 % of anaerobic strains are resistant to metronidazole. The problem of resistance of anaerobic bacteria to other antibacterial drugs has not been sufficiently studied. Conclusion. It is necessary to develop therapeutic approaches based on current data on the resistance mechanisms of non-sporeforming anaerobic bacteria.